Research progress of cyst plug in the treatment of large jaw cyst - YANG Li; ZHANG Xueming; KANG Feiwu (Kouqiang hemian waike zazhi)
Decompression is a surgical method for the preservation treatment of large jaw cysts, and a cyst plug with excellent performance is a necessary condition to ensure the therapeutic effect of this method. Making drainage port through cyst plug, balancing the pressure inside and outside the cyst cavity, and washing with postoperative physiological saline can effectively reduce the volume of the cyst cavity, and reduce the risks of nerve injury, adjacent tooth and tooth germ injury and pathological fracture of jaw caused by traditional radical surgery. In this paper, the classification and application of common cyst plugs after fenestration decompression of large jaw cysts, and the application of cyst plugs combined with negative pressure suction in recent years are reviewed.